Difficulties In Managing Methemoglobinemia - Prabhakar K; Anitha A; Rumaisa Ahmed (Journal of Clinical and Biomedical Sciences)
Acute poisoning with nitrobenzene causing significant methemoglobinemia is a rare yet life-threatening emergen-cy. A 20-year-old, female presented to Emergency in altered sensorium with a history of consumption of a bioor-ganic formulation. On examination she was cyanosed restless and agitated with SpO2 of 70% on room air. Blood samples drawn for ABG was chocolate brown colour on blotting paper. ABG showed metabolic acidosis with a satu-ration of 80%. Methylene blue 50mg in IV saline was given over 5 mins and oral ascorbic acid. She improved slowly after the 9th day with SpO2 of 92% on room air. She was discharged on the 17th day on oral iron, ascorbic acid, and breathing exercises. Early aggressive management of severe poisoning, strongly suspected on clinical grounds may change the outcome of the patient. Key-words: Nitrobenzene, methemoglobinemia, methylene blue, pulse oximetry